Relationship between the Affordances for Motor Behavior of Schoolchildren (AMBS) and Motor Competence Assessment (MCA) in Brazilian Children - Fábio Saraiva Flôres; Luis Paulo Rodrigues; Rita Cordovil (MDPI AG, 2021)
During growth, children are influenced by an extensive network, in which more favorable contexts provide better affordance landscapes, and consequently have a better potential to foster child development. We aimed to examine the affordances provided to children using the Affordances for Motor Behavior of Schoolchildren (AMBS) tool, estimating its association with children's motor competence, as assessed by the Motor Competence Assessment (MCA) battery. Seventy-two Brazilian children were evaluated using the MCA instrument. Their parents/guardians completed the AMBS. The correlations between the two instruments (sub-scales and total scores) were investigated. ANOVAs were used to compare the motor competence performance of children with Low, Average, and High AMBS scores. Positive associations were found between AMBS and MCA, although weak to moderate in nature. In addition, children whose environments were richer in motor affordances (higher AMBS scores) showed significantly higher levels on the MCA. This study provides evidence that AMBS is a valid tool for assessing motor affordances for schoolchildren, and that those affordances are related to children's motor competence.